Bovine natural killer cells are present in Escherichia coli infected mammary gland tissue and show antimicrobial activity in vitro. (October 2016) - Sipka, Anja; Pomeroy, Brianna; Klaessig, Suzanne; Schukken, Ynte
Highlights: NK cells detected in bovine mammary gland after experimental E. coli infection. Milk from healthy and infected quarters contained NK cells. E. coli stimulated bovine mammary gland epithelial cells induced NK cell migration. Bovine blood NK cells showed antibacterial activity against E. coli in vitro . Abstract: Natural killer (NK) cells are early responders in bacterial infections but their role in bovine mastitis has not been characterized. For the first time, we show the presence of NK cells (NKp46 + /CD3 − ) in bovine mammary gland tissue after an intramammary challenge with Escherichia (E.) coli . A small number of NK cells was detected in milk from quarters before and during an E. coli challenge. In vitro cultures of primary bovine mammary gland epithelial cells stimulated with UV irradiated E. coli induced significant migration of peripheral blood NK cells (pbNK) within 2 h. Furthermore, pbNK cells significantly reduced counts of live E. coli in vitro within 2 h of culture. The results show that bovine NK cells have the capacity to migrate to the site of infection and produce antibacterial mediators. These findings introduce NK cells as a leukocyte population in the mammary gland with potential functions in the innate immune response in bovine mastitis.